Effects of nano-scale nutrients supplement on natural productivity of Thalassiosira sp. and growth performance of Pacific white shrimp, Litopenaeus vannamei, reared under intensive conditions using concrete tank culture system - Romi Novriadi; Rifqi Fadhilah; Aldy Eka Wahyudi; Dea Ananda Prayogi; Ilham Ilham; Sunil Nanda (Jurnal Akuakultur Indonesia)
ABSTRACT